Structure and properties of solid BK6-OM alloy after electrosintering - Prokopiv, N.M.; Gevorkyan, E.S.; Vovk, R.V.; Harchenko, O.V.; Chishkala, V.A. (Functional Materials, 2018)
In the paper we describe the results of the structure formation and physicomechanical properties of WC-Co hard alloy from he standard especially fine-grained BK6-OM mixture of KZTS (Russia) in electrosintering (ES) process with the use of a constant electric current (I = 3000 A) in a graphite mold in vacuum under pressure of 40 MPa and temperatures above (1320°C) and below (1220°C) of the solidus line of phase diagram. For comparison, samples from this mixture are sintered according to the standard technology in vacuum. The advantage of ES in conditions of the solid phase interaction (1200°C) is shown for obtaining the two-phase structure of hard alloy with high-density, without signs of recrystallization of carbide grains, from the standard mixture of BK6-OM, which increases by 30 % the thermal conductivity, hardness, and fracture toughness compared to the Sun. The mechanism of destruction of the samples after ES in conditions of impact loading is established.